Efficient Photocatalytic Hydrogen Generation from Water over CdS Nanoparticles Confined Within an Alumina Matrix. Issue 11 (16th August 2017) - Zhou, Peng; Liu, Yuanyuan; Wang, Zeyan; Wang, Peng; Qin, Xiaoyan; Zhang, Xiaoyang; Huang, Baibiao; Dai, Ying
Abstract: In this work, CdS nanoparticles embedded in an alumina matrix were successfully synthesized using layered double hydroxides (LDHs) as the precursor and template, denoted as CdSLDH . The as‐prepared CdSLDH were characterized by XRD, UV/Vis diffuse reflectance spectroscopy, TEM, HRTEM, X‐ray photoelectron spectroscopy, photoluminescence and time‐resolved fluorescence spectra. The photocatalytic hydrogen evolution rate over CdSLDH is much higher than its counterpart without the alumina matrix, that is, almost two times higher under the same conditions. The enhanced hydrogen generation performance can be attributed to the segregation and growth‐inhibiting effects of the alumina matrix. In addition, CdSLDH also displays strong fluorescence properties and a long lifetime of photogenerated charge carriers. Abstract : Buried deep : CdS nanoparticles (diameter 5–6 nm) embedded in an alumina matrix (CdSLDH ) were synthesized using layered double hydroxides (LDHs) as the precursor and template. A key role of the alumina matrix is to suppress the further growth and aggregation of CdS nanoparticles, which in turn display improved photocatalytic activity and a longer photogenerated charge‐carrier lifetime.